Communicative Grammar Teaching Techniques - Yakubova Lobar Gulamovna (Euro Asian Journal Publishing, 2024)
This paper explores the importance of communicative grammar teaching techniques in second language acquisition. It argues that traditional grammar instruction, focused on isolated rules, falls short in fostering fluency and practical language use. The article then examines various communicative techniques, including task-based learning, games, and role-playing activities, highlighting their effectiveness in promoting meaningful grammatical understanding within a communicative context.
Keywords: Communicative; Learning; Role-Playing